A Framework for Innovative Culture Identification - Barbora Zemanova; Michaela Kotkova Striteska; David Zapletal (Journal of Competitiveness, 2022)
Innovation is a valued intangible asset that is important for a company’s competitiveness. A crucial part of corporate success is the creation of cultural values that foster innovation and creative behavior. Through a thorough review of previous articles, a scientific research gap in the literature regarding the relationship between organizational culture and organizational innovativeness has been identified. Based on resource-based view theory, the authors investigate theoretically and empirically the area of innovative culture attributes. The mixed research approach was used to examine evidence and the importance of innovative culture attributes and to determine differences between the view of managers and employees in rating innovative culture attributes at innovative large-size enterprises operating in the Czech Republic. In the first phase of the research, a qualitative personal semi-structured interview with managers responsible for innovation and change management was conducted to verify the use of proposed characteristics in companies. Then, a questionnaire survey was used to collect data and assess the importance of using identified characteristics of innovative culture. The data were statistically tested, and the results revealed the use of innovative culture attributes. Cluster analysis indicated which attributes should be used in tandem to maximize each attribute's potential. Based on these findings, a framework that defines the structure of innovative culture was created and can be used to diagnose the extent of a company's attempt to build an innovative culture.